KONSUMSI ; ANTARA AGAMA, RITUAL DAN TRANSFORMASI BUDAYA - Susminingsih, Susminingsih (I-Economics, 2017)
This paper focus on consumption behavior analysis as individual and social need. One’s identification process to his or her community often to influence their consumption decision. Analysis show that in order to understand the consumption behavior, it’s need a social-psychology-relational than economy transactional. Meaning of ethic which source on religion, have many things. Social status security is more important than individual religious satisfaction. Culture transformation being the most reason in each society. Consumption not only as need but also as a ritual which someone must do it as member in such society